Comparison of percutaneous closure systems for large bore vascular access sites in endovascular procedures - Košak, Luka; Lulić, Davorka; Jakljević, Tomislav; Gobić, David; Aničić, Josip; Tomulić, Vjekoslav (Frontiers in Cardiovascular Medicine, 2023)
Backgrounds The vascular closure device (VCD) is a medical device used for achieving hemostasis of vascular access sites greater than 8 Fr. We compared complications after placement of Perclose ProGlide (Abbott Vascular, USA), a percutaneous suture-mediated closure system, with MANTA VCD (Teleflex Vascular, USA), a collagen-based closure device. Methods This retrospective cohort study analyzed procedures performed between 2016 and 2021. We compared the incidence of bleeding complications according to the Bleeding Academic Research Consortium (BARC) and Valve Academic Research Consortium-3 (VARC-3) criteria. The comparison was made between two cohorts of patients: in the first, vascular access sites were closed with a double Perclose ProGlide system, and in the second with an 18 Fr MANTA VCD. Results A total of 189 patients were included in the study, out of which 63% were male and 37% were female, with a median age of 79 (72–83) years. All devices were used for femoral arterial access closure. A double Perclose ProGlide was used in 91 (48%) patients, while MANTA VCD was used in 98 patients (52%). The distribution of patients by VARC-3 and BARC bleeding criteria differs between groups (p = 0.017). A significantly higher incidence of VARC 1 (14% vs. 4%; p = 0.020) and BARC 1–2 (14% vs. 4%; p = 0.020) complications in the Perclose ProGlide cohort was observed. VARC 3 (1% vs. 5%; p = 0.213) and BARC 3b (1% vs. 5%; p = 0.213) complications showed higher, but statistically non-significant rates of major bleeding complications in the MANTA VCD cohort. The need for subsequent surgical revision did not show a significant difference between the cohorts (2% vs. 6%; p = 0.281). Conclusion The Perclose ProGlide cohort was associated with a significantly higher rate of milder complications. MANTA VCD cohort had a higher rate of major bleeding complications, requiring more complex treatment with a potentially larger impact on quality of life.